Feeding Habits and Trophic Niche Overlap of Aquatic Orthoptera Associated with Macrophytes - Capello, Soledad (2012)
Fil: Capello, Soledad. Instituto Nacional de Limnología (INALI-CONICET-UNL). Santa Fé; Argentina